2014
DOI: 10.1016/j.redox.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol: A modulator of the phagocyte NADPH oxidase activity - A cell-free study

Abstract: The NADPH oxidase Nox2, a multi-subunit enzyme complex comprising membrane and cytosolic proteins, catalyzes a very intense production of superoxide ions O2•−, which are transformed into other reactive oxygen species (ROS). In vitro, it has to be activated by addition of amphiphiles like arachidonic acid (AA). It has been shown that the membrane part of phagocyte NADPH oxidase is present in lipid rafts rich in cholesterol. Cholesterol plays a significant role in the development of cardio-vascular diseases that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…This is in accordance with our transcriptomic results since beef tallow is highly hypercholesterolemic [33]. Specifically, it was observed that cholesterol at high concentrations triggers inhibition of the activity of NADPH oxidase in the presence of pro-inflammatory signals [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with our transcriptomic results since beef tallow is highly hypercholesterolemic [33]. Specifically, it was observed that cholesterol at high concentrations triggers inhibition of the activity of NADPH oxidase in the presence of pro-inflammatory signals [32].…”
Section: Discussionsupporting
confidence: 92%
“…However, due to the difficulty of reliable quantitative ROS detection, this issue remains not well understood and requires further investigations [31]. Interestingly, recently, it has been shown that cholesterol is a modulator of the phagocyte NADPH oxidase activity [32]. This is in accordance with our transcriptomic results since beef tallow is highly hypercholesterolemic [33].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we have used a construction called trimera, which consisted of the following domains Nter-p47 phox (amino acids 1-286) linked to the N-ter p67 phox (amino acids 1-212), and the full length Rac1 Q61L [ 44 ]. In a previous paper, we have verified that the rates of production of superoxide anions were similar when the classic cytosolic proteins are replaced by trimera protein to activate the cyt b558 and also that the dependences of the activity in function of the enzyme activator AA concentration were also found comparable with the cytosolic fractions and the trimera [ 45 ]. Thus, the trimera was chosen in order to avoid complications due to some assembly steps and to activate the cyt b558 in a reproducible manner.…”
Section: Introductionmentioning
confidence: 75%
“…It has been reported that disruption of lipid rafts resulted in the downregulation of NADPH oxidase subunits in breast cancer cells [27] and in a compromised superoxide production [28], while lipid rafts have also been shown to maintain NADPH oxidase in an inactive state [29]. We could also observe that sterolenriched membranes decrease the rate of superoxide anion produced by recombinant NADPH oxidase [30,31]. This might be explained by different types of lipid raft redox platforms as described in [32].…”
Section: Accepted Manuscriptmentioning
confidence: 58%